Explaining the migration of stocks from exchanges in emerging economies to international centres - Stijn Claessens; Daniela Kingebiel; Sergio L. Schmukler (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
The purpose of the study is two-fold. First, it examines whether Internet usage converges across the geographical space comprising the European Union and Central and Eastern Europe (CEE). Second, it aims to expand the currently rather limited empirical evidence on the determinants of Internet usage. With regards to convergence, the data show β and σ convergence over the period 1995 to 2001, although the speed of convergence is low. The empirical analysis of the determinants of Internet usage across CEE shows that the state of liberalization of the telecommunications sector and the state of political and civil freedoms are important factors in addition to the more traditional variables such as per capita income, openness to foreign influences and education. – Internet ; transition economies ; institutions ; communication technology
Keywords: G15; G18; G20; 330; Börse; Internationaler Finanzmarkt; Finanzplatz; Welt